The Challenge of the Equivalence of Some Grammatical Constructs in the Definition Based on the Theory of Formal Change of Katford - Ghader Pariz (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2018)
Equivalence means the search for expressions and expression templates and the commanding roles of the target language for the words and constructs of the sentence of the source text. Considering the importance of this issue, the present article carefully evaluates the equivalence of some of the grammatical roles, including the structures used in it, to examine the challenges and differences in the translation from Persian to Arabic. Slow and show problems. In this regard, most examples are from two classic Persian novels, "The Director of the School" from Jalal Al-Ahmad and his "Ayes" from the Bozorg Alawi, which can be said to be indicative of the standard language. This paper, by descriptive-analytic method, examines the process of translation and equivalence of grammar and change of expression based on the theory of formal change of Katford, and it is based on the data that the interpreter should not seek to find a grammatical role Similar to the target language, it should also identify a semantic relation between two or more words in the Persian language. Then, follow the same semantic relation between the words in the Arabic language, which the theory of Katford also confirms the same difference in grammatical roles.